Tunable broadband polarization converters based on coded graphene metasurfaces - Khajeh, Ali (Sci Rep, 2021)
In this paper, two optimization algorithms (randomly initialized hill climbing and genetic algorithms) are considered to design broadband polarization converters based on coded metasurfaces. A pixeled graphene patch with an elliptic structure is proposed for the initial solution. Each pixel can be 1 and 0 which represents the presence and absence of the graphene. The initial guess tends to the optimum configuration after several optimization processes. Four broadband polarization converters are designed utilizing the optimization algorithms. By changing the chemical potential of graphene, the operation frequency of the polarization converters can be adjusted. Furthermore, the effects of relaxation time of graphene and incident angle on the polarization conversion bandwidth of the four designed structures are investigated.